Aggression as a Correlate of Examination Malpractice Proneness Among Secondary School Students in Enugu State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study was to investigate aggression as correlate to examination malpractice proneness among secondary school students in Enugu state. Correlation design was adopted for the study. It was guided by two research questions and hypotheses respectively selected from some aggression triggers like use of physical threat and weapon. The population for the study consisted of all the 15,150 senior secondary school three (SS3) in the 289 public secondary schools in both urban and rural locations of Enugu state. The sample for the study was 600 senior secondary school three (SS3) students. Purposive and simple random sampling technique was used to draw the sample. The instruments for data collection were researcher constructed scale for examination malpractice and aggression scale. The instruments were validated by three research experts. A reliability coefficient of 0.79 and 0.78 were obtained respectively using Cronbach Alpha. Pearson product moment correlation was used to answer the research questions while test of hypotheses was analyzed using T-test at 0.05 level of significance. Major findings of the study indicated that aggression have both strong and weak correlation on examination malpractice proneness. There was no significant difference in relationship between aggression and examination malpractice proneness among rural and urban secondary school’s students in Enugu State. It was recommended among other things that aggression triggers should be modulated in order to bring about decrease in examination malpractice proneness among secondary school students in Enugu state.